Analysis Speaking Skill of Goodnight Application Users - Gultom, Vica Annisah; Siregar, Nurhafni (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
The purpose of this research is to determine the speaking skill of goodnight application users. The focus of this research is to describe and analyze users speaking skills in using the goodnight application, how their speaking skills are after using the goodnight application, what features they use and how long they are active in these features. The research design is descriptive with a qualitative approach. The subjects of this research were 10 users of the goodnight application. To analyze the speaking skills of goodnight application users. Researchers used interviews by asking several questions to the users of the goodnight application.The researcher found that most users are able to speak English after using the goodnight application. The findings of this research shows that most users are able to use English, their speaking ability increases after using the goodnight application. They are quite capable of speaking English when discussing daily life.  Based on the results of the analysis, is the researcher concludes that goodnight application users are able to use English. Users also agree that the goodnight application is able to improve speaking abilities.